PERBEDAAN PERLAKUAN PPN ATAS PENGKREDITAN PAJAK MASUKAN BAGI WAJIB PAJAK YANG MASIH DALAM MASA PRA PRODUKSI DENGAN WAJIB PAJAK YANG SUDAH BERPRODUKSI - Widjaja, Gunawan; Abadi, Songga Aurora; Wicaksono, Deny (Integrative Perspectives of Social and Science Journal, 2025)
The tax system in Indonesia adheres to the principle of “Self Assessment,” whereby taxpayers' calculations of their tax withholding, payment, and reporting obligations are considered accurate until a Tax Audit Order is issued by the Directorate General of Taxes of the Ministry of Finance of the Republic of Indonesia. Furthermore, tax treatment in Indonesia must reflect fairness for every person (taxpayer) as mandated by Article 28D paragraph (1) of the 1945 Constitution, and the hierarchy of laws and regulations below it must not conflict with the 1945 Constitution. This is expected to create legal certainty and a business-friendly environment, ultimately improving the welfare of Indonesian citizens through increased state revenue from the tax sector for national development and fostering a healthy business climate. The researcher will conduct a case study on the differences in VAT treatment of input tax credits for taxpayers who are still in the pre-production phase and taxpayers who are already in production, using a normative legal approach in the research. The objective of this research is to examine the application of VAT treatment by minimizing “gray areas” and “multiple interpretations” of a provision in legislation, thereby creating legal certainty that is fair and just. It is hoped that the results of this study will create conditions where tax regulations do not conflict with higher-level regulations, thereby avoiding harm to taxpayers.